A reconsideration on regional convergence in Mexico - Ayala Gaytán, Edgardo A.; Chapa Cantú, Joana C.; Murguía Hernández, Juan D. (Estudios Económicos de El Colegio de México, 2011)
This study contrasts the traditional tests for regional convergence in Mexico, those applied on cross-section data as long as the ones built in cointegration in time series, with a new approach based in the trend in the income gap regarding a leader state. Applying this method we show that the majority of the state economies closed their gap, both to the national or the leading state per capita income, on average for the period 1940 to 2006, supporting the existence of regional convergence in Mexico at least for a critical mass of states.